Discovery of IDO1 inhibitors containing a decahydroquinoline, decahydro-1, 6-naphthyridine, or octahydro-1H-pyrrolo[3, 2-c]pyridine scaffold. (1st October 2021) - Yu, Wensheng; Deng, Yongqi; Sloman, David; Li, Derun; Liu, Kun; Fradera, Xavier; Lesburg, Charles A.; Martinot, Theo; Doty, Amy; Ferguson, Heidi; Richard Miller, J.; Knemeyer, Ian; et al.
Graphical abstract: Abstract: A series of IDO1 inhibitors containing a decahydroquinoline, decahydro-1, 6-naphthyridine, or octahydro-1H-pyrrolo[3, 2- c ]pyridine scaffold were identified with good cellular and human whole blood activity against IDO1. These inhibitors contain multiple chiral centers and all diastereomers were separated. The absolute stereochemistry of each isomers were not determined. Compounds 15 and 27 stood out as leads due to their good cellular as well as human whole blood IDO1 inhibition activity, low unbound clearance, and reasonable mean residence time in rat cassette PK studies.